اللعب وأهميته كبرنامج علاجي عند الطفل ذوي الاحتياجات الخاصة - صحراوي, وافية; كحول, سعاد (جامعة الوادي - University of Eloued, 2021)
يتداخل مفهوم ذوي الاحتياجات الخاصة في القصور اوالتدني في أداء الطفل على مستوى جانب أو عدة جوانب حياته، سواء كانت الجسمية، المعرفية، الاجتماعية، اللغوية والنفسية، لهذاأعطيت لهما أهمية كبيرة من مختلف الفئات الاجتماعية على اختلاف اختصاصاتهم، الأطباء ،علماء النفس والتربية وعلماء الاجتماع والمعلمين وأولياء الأمور والمختصين الارطوفونيين بصفة خاصة نضرا لتعدد الاختصاصات المتواجدة في هذا التخصص، وتدخلنا هو ضمن تطوير برامج واستراتيجيات التكفل بذوي الاحتياجات الخاصة وعرض التجارب الناجحة مع هذه الاخيرةThe concepts of learning disability and special needs overlap in a child's underachievement in one or more aspects of his or her life, whether physical, cognitive, social, linguistic or psychological, and have received great prominence from different social groups in different areas of competence. Physicians, psychologists, sociologists, teachers, parents and Aristotelian specialists in particular grapple with the multiplicative disciplines of this specialization, and our intervention is in the development of programs and strategies to meet special needs, and of present successful experiences with them
Play and its importance as treatment program for children with special needs
مقال
Keywords: اللعب ، برنامج علاجي ، الطفل ذوي الاحتياجات الخاصة; Play, treatment program, children with special needs